International legal issue of liability for environmental contamination (analysis and proposals) (Journal of actual problems of jurisprudence, 2018)
This article discusses one of the most pressing and complex in modern international law and requiringits scientific development – the problem of State responsibility. A very complex issue that arises whenconsidering the issue of liability for environmental damage, is the question of the fault of the state, one ofthe most controversial in the doctrine of general international law, in particular in international space law.Keywords: environment, space debris, the international legal responsibility, space activities.